Identification of Peak Vibration Velocity from Passing Vehicles on Heritage Building - Mohammad Khalis, Nuruzzahra; Tuan Chik, Tuan Norhayati; Yusoff, Nor Azizi; Shamsudin, Mustaffa Kamal; A Rahman, Nurul’Ain (Recent Trends in Civil Engineering and Built Environment, 2021)
The vibrations from the traffic have become the main concern due to the increasing traffic volume. Hence, the vulnerability of heritage building may be affected by additional stresses from vibration wave from traffic.  This study is conducted to analyse the highest velocity of vibration of the road traffic to heritage building in Muar and compare it to the limit set by department of Environment Malaysia (DOE): Malaysia Vibration guidelines. The case study took place at Old Telekom building, Muar with 23 m x 33 m x 7.5 m (length x width x height). Finite Element Modelling (FEM) was performed using BEAM4 and SHELL63 in ANSYS software and modal analysis was calculated using Block Lanczos in ANSYS software. Field vibration measurement was conducted to obtain the highest vibration velocity from traffic using smartphone with iDynamics application.  The deformation of slab and beam was found to be critical at second floor due to timber beam characteristics. Velocity vibration response was found to be decreased with the increase in distance. Peak vibration velocity was found to be 0.6 mm/s lower than 3 mm/s which considered as safe. It is also found that the peak vibration velocity, 0.6 mm/s was lower than the recommended limit for traffic-induced vibration for heritage building, 1 mm/s.  Therefore, potential damage to the building was insignificant and no effect to the building’s safety. Nevertheless, same resolution sensor and proper instrument were required for more accurate reading.